Evaluation of Cellulolytic Endo-1,4-B-D-Glucanase Activity in the Digestive Fluid of Adult Phytophagous Beetle Hoplasoma unicolor - Mohammad Mosleh Uddin; Suzana Afrin Lima; Tanim Jabid Hossain; Newton Kar; Yeasmin Zahan; Babamale AbdulKareem Olarewaju (Tropical Life Sciences Research, 2021)
Insects of the taxonomic order Coleoptera are recognised for considerable cellulolytic activity in their digestive fluid. The cellulolytic activity of the gut fluid in Hoplasoma unicolor, a member of Coleoptera, however, remains unexplored. In this study, we, for the first time, report the qualitative and quantitative analysis of cellulolytic activity in the digestive fluid of this insect. The cellulolytic endo-1,4-?-D-glucanase activity was confirmed in the supernatant of the insect’s digestive fluid by agar plate assay using carboxymethyl cellulose as the substrate. To determine the optimum pH, enzyme activity was further assessed in an acidic pH range of 5 to 6, and the highest activity was observed at pH 5.3. For quantitative analysis, endoglucanase activity was measured using 3,5-dinitrosalicylic acid method which revealed that the specific activity of the gut sample was 0.69 (±0.01) units per mg of protein. For further characterisation of the cellulases in the sample, SDS-PAGE and zymogram analysis were carried out. Two active cellulolytic bands were detected on the zymogram suggesting the presence of two distinct endoglucanases which completely disappeared upon heating the sample at 55°C. Our study, therefore, highlights prospect of the gut fluid of H. unicolor as an important source of cellulase enzymes that merits further investigations into their extensive characterisation for potential industrial applications.